The Government Efforts To Increase Public Awareness In Making Death Certies At The Department Of Population And Civil Registration In Lahat District - Yuliana Yuliana (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The author focuses on the problem of reducing mortality due to low public knowledge about making death certificates. The purpose of this study was to find out the government's efforts to increase public awareness in making death certificates at the Population and Civil Registration Office of the Lahat Regency. The research method used is qualitative by way of descriptive presentation. In collecting data, the authors use observation, open interviews, and documentation. The theory used in this career is the theory put forward by Benjamin Bloom based on Notoatmodjo (2014: 139) Regarding public awareness he divides it into three dimensions: knowledge, attitudes, and behavior. Public awareness is still low, based on a study of public awareness in issuing death certificates. Public awareness is still low. This is evidenced by the table of death certificates which increases and decreases every year. Death certificates are still considered a small document in society, so many people make death certificates because they need them for insurance payments and inheritance purposes. Therefore the Department of Population and Civil Registration of Lahat Regency carried out innovations and outreach to increase public knowledge of the importance of making death certificates.